Pengembangan Teknologi Enterprise Resource Planning Modul Accounting Management dan Supply Chain Management Pada Konter Alfarezi Berbasis Web - Rahmah, Sri; Riyadi, Slamet (TIN: Terapan Informatika Nusantara, 2021)
The rapid development of information technology greatly affects the development and progress of a business. To be able to keep pace with the development of this technology, every business must create a good and computerized system in order to help deliver accurate, fast and reliable information. Things that support being able to make a good and computerized system are from designing a good and correct database so that in the process of data entry, data calling, data retrieval, and reporting can be done quickly and easily. In managing a business, the profits obtained are not only measured by the income earned, but it is also important for a well-organized business management. There needs to be proper management so that the business being run can compete with other entrepreneurs. The system that can help manage the business being run is by using ERP (Enterprise Resource Planning) technology. This information system is a concept, technique, or method to integrate all departments and functions of a company into an entire business process automation system in order to increase the effectiveness and efficiency of the company as reflected by the existence of an accurate and measurable financial report